2006
DOI: 10.1111/j.1572-0241.2006.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Laryngitis Associated with Gastroesophageal Reflux: Prospective Assessment of Differences in Practice Patterns Between Gastroenterologists and ENT Physicians

Abstract: (1) Globus and throat clearing were considered the most useful symptoms in diagnosing GERD-related laryngitis, while laryngeal erythema and edema were considered the most useful signs for diagnosis and treatment of this condition by ENT physicians. However, these symptoms and signs may represent the least specific markers for reflux. (2) Many gastroenterologists perform pre-therapy testing which has low sensitivity in GERD-related laryngitis. (3) There is a dichotomy in treatment dose, duration, and perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 20 publications
1
72
0
6
Order By: Relevance
“…In fact, this kind of report is quite rare in the literature. Most papers dealt only with the prevalence rate of GERD (ranging 20%-50%) in patients with LPR [4,21,23,24] . Our results indicated that age, hoarseness and a hiatus hernia could be the predicting factors of LPR in the patients with RE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this kind of report is quite rare in the literature. Most papers dealt only with the prevalence rate of GERD (ranging 20%-50%) in patients with LPR [4,21,23,24] . Our results indicated that age, hoarseness and a hiatus hernia could be the predicting factors of LPR in the patients with RE.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, throat-clearing, persistent cough, globus and hoarseness are the most common complaints [24] . In our study, the prevalence of hoarseness in all the patients was 33.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The most useful laryngeal signs for LPR are reported to be erythema, oedema, presence of a posterior commisure bar and cobble stoning (Ahmed, Khandwala, Abelson et al 2006). Recent data have documented a high intra-and interobserver variability of laryngeal examination, making the laryngoscopic diagnosis of LPR highly subjective.…”
Section: Reimer and Bytzermentioning
confidence: 99%
“…There is a lack of consistent guidelines and consensus for the diagnosis of LPR (Ahmed et al 2006). The most common symptoms used to diagnose LPR include globus, throat clearing, cough, hoarseness, sore or burning throat, dysphagia, and dysphonia (Vaezi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation